Type 1 Diabetes Mellitus Diagnosed during Follow-up of Gestational Diabetes Mellitus in the Early Postpartum Period - Ikeoka, Toshiyuki (Intern Med, 2018)
A 27-year-old woman with a history of gestational diabetes mellitus (GDM) developed type 1 diabetes mellitus (T1D) in the early postpartum period. Women with a history of GDM are at an increased risk of developing T1D, which is rarer than type 2 diabetes mellitus. A postpartum follow-up 75-g oral glucose tolerance test and the measurement of glutamic acid decarboxylase autoantibodies aided in the early detection of T1D in this patient. Careful attention should be paid to women with a history of GDM who exhibit clinical features suggestive of future development of T1D.